Pengaruh Ice Breaking Berbasis Kahoot Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Matematika - Lisu, Lisu; Fitriana HS, Eka; Khaedar, Muh.; Cayati, Cayati (Lembaga Bale Literasi, 2025)
This study aims to determine the effect of Kahoot-based ice breaking activities on students’ learning motivation in Mathematics for third-grade students at UPT SPF SD Negeri Pannara. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The study involved 69 students divided into two groups: an experimental class with 30 students and a control class with 39 students. Data collection techniques included pre-tests, post-tests, motivation questionnaires, and observation sheets. Descriptive analysis results showed an increase in the average learning motivation score in the experimental class from 42.50 (Low category) to 88.40 (Very Good category) in the post-test. Meanwhile, the control class increased from an average pre-test score of 43.44 to a post-test score of 81.10 (Good category). The results of the Paired Sample T-Test and Independent Sample T-Test showed a significance value of 0.000 ≤ 0.05, indicating that Kahoot-based ice breaking activities have a significant effect on improving students’ learning motivation in Mathematics.